Darier disease: the use of dermoscopy in monitoring acitretin treatment - Catalina Silva-Hirschberg; Raúl Cabrera; María Paz Rollán; Alex Castro (Sociedade Brasileira de Dermatologia, 2022)
Abstract Darier disease is an uncommon autosomal dominant inherited disease, caused by a mutation in the ATP2A2 gene. The clinical findings are hyperkeratotic papules on the trunk, scalp, face, and neck, maceration of intertriginous areas, palmar pits, whitish papules on the oral mucosa and nail abnormalities. The main histopathologic findings are acantholysis and dyskeratotic keratinocytes. Dermatoscopic features are comedo-like openings with a central polygonal yellowish/brownish structure, surrounded by a whitish halo. First-line treatment includes acitretin. Five reports have been published describing Darier disease dermatoscopic findings. Herein, we report for the first time a patient under acitretin treatment and dermatoscopic follow-up.